Progress in the Research and Targeted Therapy of ErbB/HER Receptors in Urothelial Bladder Cancer - Chen, Dong; Ye, Yunlin; Guo, Shengjie; Yao, Kao (Frontiers in Molecular Biosciences, 2021)
Bladder cancer is a lethal malignancy, and the majority of bladder cancers arise from urothelial cells. Infiltration and metastasis are barriers for radical cystectomy to achieve favored outcomes and are the main cause of death. Systemic therapy, including chemotherapy, targeted therapy, and immunotherapy, is fundamental for these patients. ErbB/HER receptors are overexpressed in a subgroup of urothelial carcinomas, and targeting ErbB/HER receptors in these patients was found to be an efficient method in the era of genetic testing. To evaluate the role of ErbB/HER receptors in bladder cancer, we reviewed the literature and ongoing clinical trials regarding this topic to unveil the context of ErbB/HER receptors in bladder cancer, which probably helps to consolidate the theoretical basis and may instruct further research.